Extend the shelf life of fresh fruits with waxing - Dondy Anggono Setyabudi (Buletin Teknologi Pasca Panen, 2013)
Efforts to extend the shelf life of fresh fruits and vegetables have been carried out using waxing as in apple, grape, orange, longan, mango, mangosteen, guava, tomatoes, peppers, carrots, and potatoes. Waxing based on the ethanolamine, oleic acid, and water. Concentration of wax emulsions are used depending on the commodity. Waxing treatment combined with the use of fungicides. Waxing combination and intended as an effective fungicide extend the shelf life of fresh fruits and vegetables. Waxing able to form a layer on the entire surface of fruits and vegetables and cover the pores evenly. Formed a layer of wax should not interfere with physiological activity. Waxing a special treatment with the aim of replacing the natural wax ingredients in fruits and vegetables are lost during washing and improve its appearance. In the pre-transport purposes waxing intended to reduce losses and damage to the lowest possible level. Success wax coating for fruits and vegetables depending on the thickness of the layer. Although the effort to extend the shelf life of fresh fruits can be done in various ways, but waxing easier and cheaper to do. Waxing able to extend the shelf life of fresh fruits longer than the shelf life and inhibit natural deterioration. The results showed that the concentration of wax emulsions used for mangoes 6% that have the shelf life of fresh up to 3 weeks. For 6% of the mangosteen fruit with fresh shelf life up to 3 weeks. 6% for oranges with fresh shelf life to 14 days, 12% were able to maintain durian is not broken, and longan 0.25% with fresh shelf life of 7 days. Abstrak Versi IndonesiaUsaha memperpanjang daya simpan segar buah-buahan dan sayuran menggunakan pelilinan telah banyak dilakukan seperti pada apel, anggur, jeruk, lengkeng, mangga, manggis, jambu biji, tomat, paprika, wortel, dan kentang. Pelilinan didasarkan pada terbentuknya emulsi lilin melalui pengemulsian. Pengemulsian dilakukan melalui pencampuran panas dari bahan lilin, tri-etanolamin, asam oleat, dan air. Konsentrasi emulsi lilin yang digunakan bergantung komoditas buah-buahan ataupun sayur-sayuran. Perlakuan pelilinan banyak dipadukan dengan penggunaan fungisida. Kombinasi pelilinan dan fungisida dimaksudkan sebagai efektivitas memperpanjang daya simpan segar buah-buahan dan sayuran. Pelilinan mampu membentuk lapisan pada seluruh permukaan buah-buahan dan sayuran dan menutupi pori-pori secara merata. Lapisan lilin yang tujuan menggantikan bahan lilin alami pada buah dan sayur yang hilang selama pencucian dan memperbaiki penampilan. Pada pra-pengangkutan tujuan pelilinan dimaksudkan mengurangi susut dan kerusakan sampai ke tingkat serendah-rendahnya. Keberhasilan pelapisan lilin untuk buah-buahan dan sayuran bergantung pada ketebalan lapisan. Meskipun usaha memperpanjang daya simpan segar buah-buahan dapat dilakukan dengan berbagai cara, namun pelilinan lebih mudah dan murah untuk dilakukan. Pelilinan mampu memperpanjang daya simpan segar buah-buahan lebih lama dari daya simpan alamiahnya dan menghambat penurunan mutu. Hasil penelitian menunjukkan bahwa konsentrasi emulsi lilin yang digunakan untuk buah mangga 6% mempunyai daya simpan segar mencapai 3 minggu. Untuk buah manggis 6% dengan daya simpan segar mencapai 3 minggu. Untuk jeruk 6% dengan daya simpan segar mencapai 14 hari, durian 12% mampu mempertahan tidak pecah, dan lengkeng 0,25% dengan daya simpan segarnya 7 hari.